The association between histological subtype of a first primary endometrial cancer and second cancer risk. Issue 2 (February 2019) - Rhoades, Jennifer; Vetter, Monica Hagan; Fisher, James L; Cohn, David E; Salani, Ritu; Felix, Ashley S
Abstract : Objective: To evaluate the risk of a second primary cancer after endometrial cancer according to histological subtype. Methods: Using data from the 13 National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) registries we identified women diagnosed with a primary endometrial cancer between 1992 and 2014. We calculated standardized incidence ratios (SIRs) and 95% confidence intervals (CIs) for second primary cancer risk (all anatomical sites combined and for individual anatomical sites) among patients with endometrial cancer compared with the general population, in the overall study population and according to histological subtype. Results: Among 96 256 women diagnosed with endometrial cancer, 8.4% (n=8083) developed a second primary cancer. The risk of second primary cancer was higher among patients with endometrial cancer than in the general population (SIR=1.05, 95% CI 1.03 to 1.07). We observed significantly higher second primary cancer risk among women with high grade endometrioid (SIR=1.12, 95% CI 1.05 to 1.19), serous (SIR=1.24, 95% CI 1.11 to 1.38), carcinosarcoma (SIR=1.18, 95% CI 1.02 to 1.35), mixed epithelial (SIR=1.22, 95% CI 1.06 to 1.40), and sarcoma (SIR=1.28, 95% CI 1.12 to 1.45) compared with the general population, but not for women with low grade endometrioid (SIR=1.01, 95% CI 0.98 to 1.03) or clear cell (SIR=1.09, 95% CI 0.88 to 1.33) endometrial cancer. Women with low grade endometrioid endometrial cancer had significantly lower second primary cancer risks in the gum and other mouth (SIR=0.57, 95% CI 0.30 to 0.97), lung and bronchus (SIR=0.72, 95% CI 0.66 to 0.77), and lymphocytic leukemia (SIR=0.71, 95% CI 0.54 to 0.93) while women with high risk endometrial cancer histological subtypes experienced significantly higher second primary cancer risk at several anatomical sites. Conclusions: Risk of developing second primary cancersat all anatomic sites combined and at individual anatomical sites varied according to histological subtype. Clinicians should be aware that women with different histological subtypes carry different second primary cancer risks .